Friendly persuasion [videorecording (DVD)] - Wyler, William, 1902-1981; Cooper, Gary, 1901-1961; McGuire, Dorothy, 1918-2001; Main, Marjorie, 1890-1975; Middleton, Robert, 1911-1977; Perkins, Anthony, 1932-1992; West, Jessamyn (Warner Home Video, 2001)
A heart-warming story about the day-to-day experiences of a Quaker family living in Indiana in 1862, showing their religious beliefs, their worldly temptations, their petty feuds, and their reactions in a time of crisis.